An experimental study on joining of AISI 304 SS to Cu by Nd-YAG laser welding process. (2020) - Moharana, Bikash Ranjan; Sahu, Sushant Kumar; Maiti, Anway; Sahoo, Susanta Kumar; Moharana, Tapas Kumar
Abstract: In this current study, a challenging dissimilar metal combination AISI 304 stainless steel and copper is welded by pulsed wave Nd-YAG laser welding process without use of any filler material, followed by its mechanical as well as metallurgical investigation. Macroscopic as well as microscopic examination of the weld surface and weld bead has been carried out to observe the weld penetration depth and metallurgical behavior inside the weld zone. Weld pool geometry confirms about attainment of full penetration depth in pulsed wave Nd-YAG laser and also describes that the penetration depth is directly proportional pulse energy as (penetration depth7 J = 69%) < (penetration depth14 J = 82%) < (penetration depth21 J = 100%). The formed copper micro-channels suggest that the copper solidifies last and flows inside the weld zone matrix during the solidification. The average width of the heat affected zone (HAZ) and partially melting zone (PMZ) have been found to be 23.0 µm and 6.0 µm on the stainless steel (SS) side respectively. The microhardness (MH) study shows that (MHCopper = 75 HV0.1) < (MHWeld zone = 90–200 HV0.1) < (MHSS = 210 HV0.1).